Natural hybridization and genetic and morphological variation between two epiphytic bromeliads - Neri, Jordana; Wendt, Tania; Palma-Silva, Clarisse [UNESP] (Oxford Univ Press, 2018)
Reproductive isolation is of fundamental importance for maintaining species boundaries in sympatry. Here, we examine the genetic and morphological differences between two closely related bromeliad species: Vriesea simplex and Vriesea scalaris. Furthermore, we examined the occurrence of natural hybridization and discuss the action of reproductive isolation barriers. Nuclear genomic admixture suggests hybridization in sympatric populations, although interspecific gene flow is low among species in all sympatric zones (N(e)m < 0.5). Thus, morphological and genetic divergence (10.99 %) between species can be maintained despite ongoing natural hybridization. Cross-evaluation of our genetic and morphological data suggests that species integrity is maintained by the simultaneous action of multiple barriers, such as divergent reproductive systems among species, differences in floral traits and low hybrid seed viability.
Keywords: Atlantic Forest; Bromeliaceae; floral traits; hybrids; reproductive barriers; species integrity; sympatric